Grenada : Disaster Resilience Strategy. (IMF Staff Country Reports; Country Report, 2022)
Natural disasters and climate change are existential threats to Grenada, with annual losses from these events estimated at 1.7 percent of GDP. Grenada has proactively pursued resilience-building, with its Climate Change Policy and National Adaptation Plan providing detailed roadmaps for policymakers. However, the challenges are increasing, including from slow-moving effects owing to the rising sea level, even as implementation capacity and resource constraints remain significant impediments. The COVID-19 pandemic has amplified those challenges by increasing risks and tightening Grenada's fiscal space.